2010
DOI: 10.5539/mas.v4n5p105
|View full text |Cite
|
Sign up to set email alerts
|

Aloe Plant Extract as Environmentally Friendly Inhibitor on the Corrosion of Aluminum in Hydrochloric Acid in Absence and Presence of Iodide Ions

Abstract: The study shows that the corrosion of Aluminum increases with increasing HCl concentration which indicates the dependence of Aluminum corrosion on the concentration of HCl .The inhibition efficiency of the corrosion by Aloe extract was found to increase with the increase of Aloe extract concentration. Its inhibitive action from chemical (hydrogen evolution and mass loss) and electrochemical (polarization and impedance) was in good agreement. Also, it was found that Aloe plant act as mixed type inhibitor. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…Figures 8-9 show the linear regression of logCR and 1/ and logCR/ and 1/ for the specimen immersed in sulphuric acid with and without inhibitor [5,6]. From the Table 6, the results showed that the apparent activation energy in the absence of inhibitor is lower than that in the presence of the inhibitor which implies physiorption adsorption isotherm [7,8] and this suggests that the anticorrosion inhibitor is very active for mild steel in acidic medium. …”
Section: 2mentioning
confidence: 91%
See 1 more Smart Citation
“…Figures 8-9 show the linear regression of logCR and 1/ and logCR/ and 1/ for the specimen immersed in sulphuric acid with and without inhibitor [5,6]. From the Table 6, the results showed that the apparent activation energy in the absence of inhibitor is lower than that in the presence of the inhibitor which implies physiorption adsorption isotherm [7,8] and this suggests that the anticorrosion inhibitor is very active for mild steel in acidic medium. …”
Section: 2mentioning
confidence: 91%
“…Recently considerable interest has been generated in the use of nitrogen, oxygen and sulphur containing organic compounds as corrosion inhibitor for mild steel in different acids [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to protect the integrity of the aluminum surface in an aggressive acid medium or other corrosive environment. In recent decades, the addition of inhibitors has been considered to be the most common approach to hinder the corrosion of aluminum [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…From the stock solution, 2-10% concentration of the extract was prepared using 1N hydrochloric acid. Similar kind of preparation has been reported in studies using aqueous plant extracts in the recent years [21][22][23][24][25][26][27][28][29][30].…”
Section: Preparation Of the Plant Extract The Leaves Of The Plantsmentioning
confidence: 74%